1983
DOI: 10.1093/infdis/148.5.785
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cell-Mediated Cytotoxicity Against Influenza Virus-Infected Cells

Abstract: The three major immunocompetent cells in human peripheral blood (lymphocytes, neutrophils, and monocytes) were shown to be effector cells for antibody-dependent cell-mediated cytotoxicity (ADCC) against influenza virus-infected baby hamster kidney cells in vitro. Lymphocyte cytotoxicity was mediated by FcIgG receptor-bearing null cells and T gamma cells. These effector populations were best defined by HNK-1, a monoclonal antibody to human natural killer and ADCC-mediator cells. Antibody responsible for ADCC ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 22 publications
4
101
0
Order By: Relevance
“…The role of neutralizing and non-neutralizing Abs in effector cell activation is highly dependent on the affinity of these antibodies to the Fc gamma receptor. Differences between HA binding and binding to live virus could be explained by the presence of ADCC-inducing antibodies directed against structural proteins present on the surface of infected cells, such as NP or M2 (Hashimoto et al, 1983;Jegerlehner et al, 2004;Lamb et al, 1985). Besides the target of the antibodies, the accessibility of epitopes might play a role.…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 99%
“…The role of neutralizing and non-neutralizing Abs in effector cell activation is highly dependent on the affinity of these antibodies to the Fc gamma receptor. Differences between HA binding and binding to live virus could be explained by the presence of ADCC-inducing antibodies directed against structural proteins present on the surface of infected cells, such as NP or M2 (Hashimoto et al, 1983;Jegerlehner et al, 2004;Lamb et al, 1985). Besides the target of the antibodies, the accessibility of epitopes might play a role.…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 99%
“…The highest serum dilution showing > 15% SIL was defined as the ADCC endpoint titer. In a previous paper, Hashimoto et al used 10% as a cutoff (7). For calculation of mean endpoint titers, an undetectable ADCC titer was assigned a value of 5.…”
Section: Assaymentioning
confidence: 99%
“…In an early study by Hashimoto et al, ADCC antibodies were detected at higher levels (1 to 2 log10) than HAI antibodies after experimental live attenuated intranasal influenza vaccination in young children; these antibodies were detected earlier and were broadly cross-reactive within a subtype (7). Similarly, Vella et al reported that adult subjects who received the A/Victoria/3/75(H3N2) inactivated influenza vaccine showed a significant rise in ADCC specific immune lysis (SIL) and developed ADCC antibody titers similar to naturally infected subjects (27).…”
Section: Introductionmentioning
confidence: 95%
“…The narrow specificity of influenza NAbs, particularly those directed against the immunodominant hemagglutinin (HA) head, is problematic for protection against influenza viruses (14,15). However, in addition to neutralization, Abs can also mediate several functions through their Fc region, including complement-dependent cytotoxicity (CDC) (16,17), Ab-dependent cellular cytotoxicity (ADCC) (18)(19)(20)(21), and Ab-dependent phagocytosis (ADP) (22). ADCC occurs when Abs bind to viral antigens on infected cells and engage receptors for the Fc region of IgG (FcÎłRs) found on the surface of innate immune effector cells.…”
Section: Introductionmentioning
confidence: 99%